Pengaruh Sumber Lemak Yang Berbeda Pada Pakan Terhadap Indeks Viscera Somatik, Indeks Hepatosomatik dan Gambaran Histopatologi Hati Ikan Kelabau (Osteochilus melanopleurus) - Putri, Adeliani; Susanto, Adi; Sulistyawati, Sulistyawati (Sekolah Tinggi Pertanian Kutai Timur, 2024)
This study was conducted to determine the effect of providing different sources of lipid in feed on the values of the somatic viscera index, hepatosomatic index, and liver histopathological change of kelabau. This study used a completely randomized design (CRD) with 5 treatments with 3 repetitions with different doses consisting of the addition of 100% fish oil, 75% fish oil + 25% corn oil, 50% fish oil + 50% corn oil, 25% fish oil + 75% corn oil, and 100% fish oil. There were 20 kelabau with an average length of 5–6.5 cm and a weight of 1.5–2 grams that were kept in plastic tanks measuring 34.3 cm by 38 cm by 31.5 cm with a semi-closed water circulation system for 45 days. Fish were given treated food twice a day, in the morning and evening, for satiation. Data analysis was carried out using the variance test (ANOVA) with a confidence level of 95% and continued with further tests using the Honestly Significant Difference (HSD) test or Tukey test. The results showed that feeding with a different lipid source at a dose of 25% fish oil and 75% corn oil showed a somatic visceral index of 9.19 and a hepatosomatic index of 1.03 compared to other treatments, as well as a histopathological change of the liver showing edema in some cells, apoptosis, and lipid degeneration by ω 3 and ω 6 which is useful as energy reserves and fish growth